You're looking for a solution of the form
![\displaystyle y = \sum_{n=0}^\infty a_n x^n](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%20%3D%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20a_n%20x%5En)
Differentiating twice yields
![\displaystyle y' = \sum_{n=0}^\infty n a_n x^{n-1} = \sum_{n=0}^\infty (n+1) a_{n+1} x^n](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%27%20%3D%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20n%20a_n%20x%5E%7Bn-1%7D%20%3D%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28n%2B1%29%20a_%7Bn%2B1%7D%20x%5En)
![\displaystyle y'' = \sum_{n=0}^\infty n(n-1) a_n x^{n-2} = \sum_{n=0}^\infty (n+1)(n+2) a_{n+2} x^n](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%27%27%20%3D%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20n%28n-1%29%20a_n%20x%5E%7Bn-2%7D%20%3D%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28n%2B1%29%28n%2B2%29%20a_%7Bn%2B2%7D%20x%5En)
Substitute these series into the DE:
![\displaystyle (x-1) \sum_{n=0}^\infty (n+1)(n+2) a_{n+2} x^n - x \sum_{n=0}^\infty (n+1) a_{n+1} x^n + \sum_{n=0}^\infty a_n x^n = 0](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%28x-1%29%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28n%2B1%29%28n%2B2%29%20a_%7Bn%2B2%7D%20x%5En%20-%20x%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28n%2B1%29%20a_%7Bn%2B1%7D%20x%5En%20%2B%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20a_n%20x%5En%20%3D%200)
![\displaystyle \sum_{n=0}^\infty (n+1)(n+2) a_{n+2} x^{n+1} - \sum_{n=0}^\infty (n+1)(n+2) a_{n+2} x^n \\\\ \ldots \ldots \ldots - \sum_{n=0}^\infty (n+1) a_{n+1} x^{n+1} + \sum_{n=0}^\infty a_n x^n = 0](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28n%2B1%29%28n%2B2%29%20a_%7Bn%2B2%7D%20x%5E%7Bn%2B1%7D%20-%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28n%2B1%29%28n%2B2%29%20a_%7Bn%2B2%7D%20x%5En%20%5C%5C%5C%5C%20%5Cldots%20%5Cldots%20%5Cldots%20-%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28n%2B1%29%20a_%7Bn%2B1%7D%20x%5E%7Bn%2B1%7D%20%2B%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20a_n%20x%5En%20%3D%200)
![\displaystyle \sum_{n=1}^\infty n(n+1) a_{n+1} x^n - \sum_{n=0}^\infty (n+1)(n+2) a_{n+2} x^n \\\\ \ldots \ldots \ldots - \sum_{n=1}^\infty n a_n x^n + \sum_{n=0}^\infty a_n x^n = 0](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csum_%7Bn%3D1%7D%5E%5Cinfty%20n%28n%2B1%29%20a_%7Bn%2B1%7D%20x%5En%20-%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20%28n%2B1%29%28n%2B2%29%20a_%7Bn%2B2%7D%20x%5En%20%5C%5C%5C%5C%20%5Cldots%20%5Cldots%20%5Cldots%20-%20%5Csum_%7Bn%3D1%7D%5E%5Cinfty%20n%20a_n%20x%5En%20%2B%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20a_n%20x%5En%20%3D%200)
Two of these series start with a linear term, while the other two start with a constant. Remove the constant terms of the latter two series, then condense the remaining series into one:
![\displaystyle a_0-2a_2 + \sum_{n=1}^\infty \bigg(n(n+1)a_{n+1}-(n+1)(n+2)a_{n+2}-na_n+a_n\bigg) x^n = 0](https://tex.z-dn.net/?f=%5Cdisplaystyle%20a_0-2a_2%20%2B%20%5Csum_%7Bn%3D1%7D%5E%5Cinfty%20%5Cbigg%28n%28n%2B1%29a_%7Bn%2B1%7D-%28n%2B1%29%28n%2B2%29a_%7Bn%2B2%7D-na_n%2Ba_n%5Cbigg%29%20x%5En%20%3D%200)
which indicates that the coefficients in the series solution are governed by the recurrence,
![\begin{cases}y(0)=a_0 = -7\\y'(0)=a_1 = 3\\(n+1)(n+2)a_{n+2}-n(n+1)a_{n+1}+(n-1)a_n=0&\text{for }n\ge0\end{cases}](https://tex.z-dn.net/?f=%5Cbegin%7Bcases%7Dy%280%29%3Da_0%20%3D%20-7%5C%5Cy%27%280%29%3Da_1%20%3D%203%5C%5C%28n%2B1%29%28n%2B2%29a_%7Bn%2B2%7D-n%28n%2B1%29a_%7Bn%2B1%7D%2B%28n-1%29a_n%3D0%26%5Ctext%7Bfor%20%7Dn%5Cge0%5Cend%7Bcases%7D)
Use the recurrence to get the first few coefficients:
![\{a_n\}_{n\ge0} = \left\{-7,3,-\dfrac72,-\dfrac76,-\dfrac7{24},-\dfrac7{120},\ldots\right\}](https://tex.z-dn.net/?f=%5C%7Ba_n%5C%7D_%7Bn%5Cge0%7D%20%3D%20%5Cleft%5C%7B-7%2C3%2C-%5Cdfrac72%2C-%5Cdfrac76%2C-%5Cdfrac7%7B24%7D%2C-%5Cdfrac7%7B120%7D%2C%5Cldots%5Cright%5C%7D)
You might recognize that each coefficient in the <em>n</em>-th position of the list (starting at <em>n</em> = 0) involving a factor of -7 has a denominator resembling a factorial. Indeed,
-7 = -7/0!
-7/2 = -7/2!
-7/6 = -7/3!
and so on, with only the coefficient in the <em>n</em> = 1 position being the odd one out. So we have
![\displaystyle y = \sum_{n=0}^\infty a_n x^n \\\\ y = -\frac7{0!} + 3x - \frac7{2!}x^2 - \frac7{3!}x^3 - \frac7{4!}x^4 + \cdots](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%20%3D%20%5Csum_%7Bn%3D0%7D%5E%5Cinfty%20a_n%20x%5En%20%5C%5C%5C%5C%20y%20%3D%20-%5Cfrac7%7B0%21%7D%20%2B%203x%20-%20%5Cfrac7%7B2%21%7Dx%5E2%20-%20%5Cfrac7%7B3%21%7Dx%5E3%20-%20%5Cfrac7%7B4%21%7Dx%5E4%20%2B%20%5Ccdots)
which looks a lot like the power series expansion for -7<em>eˣ</em>.
Fortunately, we can rewrite the linear term as
3<em>x</em> = 10<em>x</em> - 7<em>x</em> = 10<em>x</em> - 7/1! <em>x</em>
and in doing so, we can condense this solution to
![\displaystyle y = 10x -\frac7{0!} - \frac7{1!}x - \frac7{2!}x^2 - \frac7{3!}x^3 - \frac7{4!}x^4 + \cdots \\\\ \boxed{y = 10x - 7e^x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%20%3D%2010x%20-%5Cfrac7%7B0%21%7D%20-%20%5Cfrac7%7B1%21%7Dx%20-%20%5Cfrac7%7B2%21%7Dx%5E2%20-%20%5Cfrac7%7B3%21%7Dx%5E3%20-%20%5Cfrac7%7B4%21%7Dx%5E4%20%2B%20%5Ccdots%20%5C%5C%5C%5C%20%5Cboxed%7By%20%3D%2010x%20-%207e%5Ex%7D)
Just to confirm this solution is valid: we have
<em>y</em> = 10<em>x</em> - 7<em>eˣ</em> ==> <em>y</em> (0) = 0 - 7 = -7
<em>y'</em> = 10 - 7<em>eˣ</em> ==> <em>y'</em> (0) = 10 - 7 = 3
<em>y''</em> = -7<em>eˣ</em>
and substituting into the DE gives
-7<em>eˣ</em> (<em>x</em> - 1) - <em>x</em> (10 - 7<em>eˣ </em>) + (10<em>x</em> - 7<em>eˣ</em> ) = 0
as required.